Penguatan Kegiatan Pembelajaran IPS melalui Social Science Vocabulary Recognition Model through Guessing Games - Eldi Mulyana; Alni Dahlena (UM Purwokerto Press, 2022)
The rapid development of learning has an influence on the learning process in the teaching unit. In the midst of current conditions, it is undeniable that it has an influence on the decline in student interest in learning. The current learning system process is through the concept of distance learning, of course, this must be followed by students, even though students experience a decrease in interest in learning and begin to feel the point of saturation in the learning process. The purpose of this study is to improve social science vocabulary recognition models through guessing games in the learning process through conditions during the adaptation period of new habits, so that it will lead to students' learning motivation, then to find out the increase in students' interest in learning social studies in the learning process at time to adapt to new habits. The research method used is a qualitative research approach by looking for data in the form of case studies on students, and direct observation on students. Data collection techniques were carried out using interview techniques, documentation techniques and case studies. Data analysis techniques were carried out through data collection, data reduction, data presentation and data verification. The results of this study have a positive impact on interest in learning and increasing social skills for students in understanding vocabulary in social studies learning. So that through learning activities during the adaptation period of new habits through the method of social science vocabulary recognition model through guessing games so that it can restore students' interest in learning during the adaptation period of new habits, especially in current learning.